Natural Fiber Incorporated Polymer Matrix Composites for Electronic Circuit Board Applications - V. S. Chandrika; A. Anamika; C. Jeeva; Bhagavathi Perumal; S. Sanal Kumar; J. Femila Roseline; Ishwarya Komalnu Raghavan (Advances in Materials Science and Engineering)
There are many more applications for fibre-reinforced epoxy composites than there are for metals and alloys today. For example, sustainable, recyclable, and biodegradable reinforcements have been used in numerous studies to improve the mechanical and thermal properties of composite materials. It was discovered that the properties of epoxy-based composites could be improved by combining biosolid waste sugarcane bagasse ash fillers, madar fibre, and epoxy resin. Conventional compression molding techniques were used to prepare the sugarcane bagasse ash (SBA) particles and madar fibre-reinforced epoxy resin-based composites (PMCs), which were loaded with varying amounts of fibre and fillers. Hybrid biocomposites were evaluated for mechanical (tensile, flexural, impact, and hardness) and water absorption characteristics. Epoxy matrix composites containing 28 wt.% madar fibre and 7 wt.% sugarcane bagasse ash fillers had tensile, flexural, hardness, and impact values of 61 MPa, 147 MPa, and 54 kJ/m2, respectively.